Effects of limited water supply on metabolite composition in tomato fruits (Solanum lycopersicum L.) in two soils with different nutrient conditions - Kim, Yangmin X.; Son, Su Young; Lee, Seulbi; Lee, Yejin; Sung, Jwakyung; Lee, Choong Hwan (Frontiers in Plant Science, 2022)
Effect of water supply to metabolites in tomato fruit was compared in two soils with different nutrient conditions, i.e. either limited or excess. Two types of soil nutrient condition, type A: nutrient-limited and type B: nutrient-excess, were prepared as follows; type A is a low nutrient soil without a replenishment of starved nitrogen and phosphorous, type B is a high nutrient soil exceeding the recommended fertilization. Soil water was adjusted either at 30 kPa (sufficient) or 80 kPa (limited). For harvested tomato fruits, we examined primary and secondary metabolites using non-targeted mass spectrometry (MS)-based metabolomics. The fruit production and leaf SPAD were greatly dependent on soil nutrient levels, by contrast, the level of lycopene remained unchanged by different levels of water and nutrient supply. The perturbation of metabolites by water supply was clear in the nutrient-excess soil. In particular, limited water supply strongly decreased primary metabolites including sugars and amino acids. We demonstrated that water stress differently shifted primary metabolites of tomato fruits in two soils with different nutrient conditions via non-targeted mass spectrometry-based metabolomics. Thus, we carefully suggest that sufficient water supply in soils with surplus nutrients is an important factor to improve fruit quality in terms of the abundance in primary metabolites such as sugars and amino acids.